El guion cinematográfico, ¿texto literario? - Pollarolo, Giovanna (2011)
The conventional and most widespread definition of the screenplay is that which regards it as a “working instrument” that “guides” the making of a film due to the presentation of a set of instructions to perform it. Clearly,such a consideration, of a purely utilitarian text to serve a “greater work” in this case the film script has been limited to its pragmatic function. This explains the absence, with few exceptions, of studies to discuss, for example, its narrative status and quality—either as “literary text” or as “minortext”—its ability or inability to be read as autonomous text, its relationship to the movie once filmed and approaches around issues of authorship,among others. In this paper I intend to challenge the conventional definition and propose some approaches going beyond the limits imposed bythis concept.